Implementasi Teknologi Tepat Guna dan Strategi Digital Marketing untuk Peningkatan Kapasitas Produksi dan Omset UMKM Kopi Boyo Jepara - Akhmad Syakhroni; Muhammad Sagaf; Andi Riansyah (Jurnal Sains Teknologi dalam Pemberdayaan Masyarakat, 2026)
This Community Service Program aims to empower the coffee MSME "VINZOEI" located in Sumanding Village, Kembang Sub-district, Jepara Regency, which has significant potential in the coffee plantation sector. The main problems faced by the partner include dependence on third-party services for coffee roasting, limited use of digital marketing, and unattractive product packaging. This program offers solutions through the application of coffee roasting machine technology to improve production efficiency and quality, internet marketing training to expand market reach, and the development of new, more appealing packaging designs to enhance product value. The program activities include socialization, training, technology implementation, mentoring, and periodic evaluations. This initiative aligns with the goals of the SDGs and ASTA CITA, and supports the achievement of key university performance indicators (IKU). It is expected that this program will help the partner increase production capacity, expand marketing coverage, and sustainably improve business assets and revenue.